Characteristics of Primary Open-Angle Glaucoma Patients in Dr. Soetomo General Hospital Surabaya - Sherly Yolanda; Yulia Primitasari; Dewi Ratna Sari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: This research aimed to describe the characteristics of primary open-angle glaucoma (POAG) patients in Dr. Soetomo General Hospital Surabaya. Methods: This was a descriptive study to determine the characteristics of POAG in 42 patients recruited from Ophthalmology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya, from March to June 2018. This study was conducted because the epidemiological data about characteristics of patients with POAG in Surabaya are not available yet. Results: The ratio of male and female patients with POAG was 1:1, the largest age group of patients was 55-64 years old (38.10%), in which a few patients had history of hypertension (45.24%). Regression of visual acuity was the most common symptoms along with clinical sign of the patients (78.57%), and the most common location of POAG was both eyes (69.05%). Furthermore, the mean of visual acuity of patients with POAG was 0.38 ± 0.36, and the mean of intraocular pressure of patients with POAG was 22.22 ± 9.24 mmHg. Conclusion: POAG is generally bilateral disease that can occur in men and women with no differences with the largest age group of 55-64 years old, the most common symptom and clinical sign was regression of visual acuity.